1992
DOI: 10.1111/j.1365-2559.1992.tb01009.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular ‘neurothekeoma’: an epithelioid variant of pilar eiomyoma? Morphological and immunohistochemical analysis of a series

Abstract: Cellular neurothekeoma is a recently recognized benign cutaneous neoplasm, which is currently regarded as being of nerve sheath origin and is thought to represent a variant of conventional neurothekeoma (dermal nerve sheath myxoma). Nine new cases presenting predominantly in adolescents or young adults are described. Morphologically they were characterized by short fascicles or small nests of palely eosinophilic epithelioid or spindle-shaped cells which ramified in an ill-defined manner between dermal collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
76
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 26 publications
5
76
1
Order By: Relevance
“…5,[9][10][11] It has, however, been noted to stain with some neural markers, including PGP 9.5, and, more interestingly, melanocyte markers, including NKI/C3. 11,12 Other studies have shown it to be smooth muscle actin positive (see Table 5). The goal of this study was to characterize the combination of Mitf and NKI/C3 expression in cellular neurothekeomas.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…5,[9][10][11] It has, however, been noted to stain with some neural markers, including PGP 9.5, and, more interestingly, melanocyte markers, including NKI/C3. 11,12 Other studies have shown it to be smooth muscle actin positive (see Table 5). The goal of this study was to characterize the combination of Mitf and NKI/C3 expression in cellular neurothekeomas.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies have also shown that cellular neurothekeoma does not actually represent a variant of neurothekeoma and is in fact a tumor of another cell type. 21 Calonje et al, 12 suggested with their immunohistochemical and light microscopic study that cellular neurothekeoma was in fact an epithelioid variant of a pilar leiomyoma. In addition, Mitf positivity has been shown in PEComas.…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…There have been many theories regarding the histogenesis of these lesions with authors regarding them as variants of dermatofibromas, leiomyomas, or nerve sheath tumors. [19][20][21][22] It has been noted that cellular neurothekeoma can resemble a melanocytic tumor by virtue of its growth pattern, but lack of expression of S100 protein was against a melanocytic origin. 12,22 It is reasonable to classify cellular neurothekeoma as fibrohistiocytic tumors, as suggested by Fetsch et al, 3 although this category is itself somewhat of a wastebasket term.…”
Section: Discussionmentioning
confidence: 99%
“…Fetsch et al postulated a tendency of NSM to recruit histiocytic cells and to differentiate into myofibroblasts [13]. SMA positivity suggests some similarity to the epithelioid variant of leiomyoma or myofibroblastic proliferations [14]. GFAP positivity is rare in NSM; however, its positivity further supports a peripheral nerve sheath origin as occasional peripheral nerve sheath tumors may co-express GFAP and S100 [15].…”
Section: Discussionmentioning
confidence: 99%